Electronic Information Seeking behavior of Education Postgraduates: A Case Study at University of Peradeniya Sri Lanka - Gunasekera, Chamani; Balasubramani, R. (Journal of Information and Knowledge, 2019)
The present study explored electronic information seeking behavior of postgraduate students in Education in relation to their scholarly activities. The present study was conducted to examine whether the postgraduates students utilize electronic resources and services provided by the library and the extent to which the library was used. A questionnaire was administered to all the postgraduate students in the Department of Education, Faculty of Arts, and University of Peradeniya, Sri Lanka in September 2017 and the data were statistically analyzed using SPSS software. The results revealed that most of the respondents used electronic resources available in the library, and websites and online catalogs are the most preferred electronic resources. This study showed that most of the respondents used e-resources for their research works and writing assignments and the average time spent for using e-resources was one to two hours per week. It is evident that most of the respondents preferred to access e-resources from the University library and the cybercafés and most of them were aware of e-resources available in the library. The study further identified some constraints users face when using electronic resources.